Professional noticing on a statistical task. (2nd January 2020) - Nagle, Courtney; Casey, Stephanie; Carney, Michele
ABSTRACT: This study explores secondary in-service mathematics teachers' professional noticing of student work on a statistical task involving informally placing a line of best fit. The manuscript describes how teachers interpreted student work on the line of best fit task, how teachers responded to the student work, and associations between their interpretations and consequential responses. Findings related to teachers' interpretations of student work revealed that teachers were often evaluative and tended to describe both students' processes and underlying understanding, although the descriptions of understanding were frequently unsupported by the work. Teachers' responses to students were typically open-ended but infrequently showed promise of moving student thinking forward to the task's learning objective. Focusing on both affordances and deficits when interpreting a student's work and drawing on student thinking when responding are two characteristics that often accompanied strong teacher responses. Results suggest it is important to provide opportunities for teachers to develop their statistical knowledge for teaching topics like line of best fit, which have received increased emphasis in current academic school standards.